2003
DOI: 10.1200/jco.2003.02.063
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcomes From Adding Sequential Paclitaxel but Not From Escalating Doxorubicin Dose in an Adjuvant Chemotherapy Regimen for Patients With Node-Positive Primary Breast Cancer

Abstract: The addition of four cycles of paclitaxel after the completion of a standard course of CA improves the disease-free and overall survival of patients with early breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
677
7
23

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,243 publications
(737 citation statements)
references
References 19 publications
25
677
7
23
Order By: Relevance
“…Furthermore, our results need to be discussed in front of the recent introduction of taxanes in the adjuvant treatment of EBC. Indeed, recent studies have clearly demonstrated a benefit in term of MFS and OS when paclitaxel or docetaxel are associated with anthracylines in chemotherapy regimen administered after primary surgery of EBC patients with lymph node invasion (Henderson et al, 2003;Nabholtz et al, 2002). However, the taxane-anthracycline combination, although effective is probably more toxic and certainly more expensive, justifying efforts to identify patients likely to be cured by conventional anthracycline-based regimen alone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results need to be discussed in front of the recent introduction of taxanes in the adjuvant treatment of EBC. Indeed, recent studies have clearly demonstrated a benefit in term of MFS and OS when paclitaxel or docetaxel are associated with anthracylines in chemotherapy regimen administered after primary surgery of EBC patients with lymph node invasion (Henderson et al, 2003;Nabholtz et al, 2002). However, the taxane-anthracycline combination, although effective is probably more toxic and certainly more expensive, justifying efforts to identify patients likely to be cured by conventional anthracycline-based regimen alone.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their significant activity in the metastatic setting [2], the taxanes have also been extensively tested in the adjuvant setting in many randomized trials [3][4][5][6][7][8]; significant improvement in efficacy outcomes in terms of disease-free survival (DFS) [4,5] and overall survival (OS) [3,6,7] has been reported. Moreover, recently, a meta-analysis of 13 randomized studies including 22,903 patients demonstrated that the addition of a taxane to an anthracycline-based regimen improves DFS and OS of high-risk early breast cancer patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…1 to receive eight cycles of FAC vs. four cycles of paclitaxel followed by four cycles of FAC. 6 The question posed by this trial was whether the initial positive results reported with the addition of paclitaxel to an anthracycline-based regimen 5 were the result of merely more chemotherapy as opposed to a specific therapeutic effect of paclitaxel. Preliminary results demonstrated a trend toward prolonged DFS at a median follow-up of 4years (83% for FAC ϫ8 vs. 86% for paclitaxel ϫ4 followed by FAC ϫ4), which did not reach statistical significance (P ϭ 0.09).…”
Section: Discussionmentioning
confidence: 99%